PANCASILA AND CHALLENGE GENERATION Z IN ERA DIGITAL - Anisia Nur Mitha Sari; Romadhona Kusuma Yudha; Elfahmi Lubis; Joesa Wulandari (PT. Jurnal Center Indonesia Publisher, 2026)
Pancasila, US the fundamental ideology of the Indonesian nation, plays a central role in shaping the character and direction of national life. However, the rapid development of digital technology presents new challenges for the younger generation generation, particularly Generation Z, in internalizing Pancasila values. This generation lives technologically amidst advancements, a culture of globalization, and the rapid flow of information. US a result, there has been a shift in values, a decline in nationalism, and an increase in individualism and social polarization. This article aims to explain how Pancasila values can be re-actualized in the lives of Generation Z in the digital era. Through a qualitative descriptive approach and literature analysis, this article highlights the importance of Pancasila education, digital literacy, and the role of educational institutions in strengthening national character. The study's results indicate that collaboration between families, schools, and communities needs to be strengthened so that Pancasila is not only cognitively understood but also practiced in the social behavior of Generation Z.